Exploiting Information Extraction Annotations for Document Retrieval in Distillation Tasks - Levit, Michael; Hakkani-Tür, Dilek; Tur, Gokhan (Interspeech, Proc. of Interspeech, 2007)
Information distillation aims to extract relevant pieces of information related to a given query from massive, possibly multilingual, audio and textual document sources. In this paper, we present our approach for using information extraction annotations to augment document retrieval for distillation. We take advantage of the fact that some of the distillation queries can be associated with annotation elements introduced for the NIST Automatic Content Extraction (ACE) task. We experimentally show that using the ACE events to constrain the document set returned by an information retrieval engine significantly improves the precision at various recall rates for two different query templates.